Effect of Paleolithic-based low-carbohydrate vs. moderate-carbohydrate diets with portion-control and calorie-counting on CTRP6, asprosin and metabolic markers in adults with metabolic syndrome: A randomized clinical trial. (April 2022) - Shemirani, Farnoosh; Djafarian, Kurosh; Fotouhi, Akbar; Azadbakht, Leila; Rezaei, Nima; Chamari, Maryam; Shabani, Samaneh; Mahmoudi, Maryam
Summary: Objective: Several recent studies have been undertaken into carbohydrate-restricted diets. it has not been clearly demonstrated whether diets with different proportions of energy from carbohydrate exert distinct effects on metabolism and inflammation or not. The current randomized clinical trial (RCT) has been conducted to further elucidate the effects of severe and mild carbohydrate restriction on inflammation and cardiometabolic status in adults with metabolic syndrome (MetS). Methods: Eighty adults with metabolic syndrome were randomized to one of the four carbohydrate restricted diets: Paleolithic-based low-carbohydrate diet with calorie-counting method (PLCD-CC) (n = 20), Paleolithic-based low-carbohydrate diet with portion-control method (PLCD-PC) (n = 20), moderate-carbohydrate diet with calorie-counting method (MCD-CC) (n = 20) and moderate-carbohydrate diet with portion-control method (MCD-PC) (n = 20) for 10 weeks. PLCD is defined as a diet consisting of 25–30% of energy from carbohydrate, 30% of energy from protein and 40–45% of energy from fat and encourages consumption of fruits, vegetables and lean meat. MCD is characterized as 40–45% carbohydrate, 30% protein and 30–35% fat. Body weight and composition, adipokines such as Asprosin, chemerin, leptin, hepatokines namely CTRP-6, FGF-21 and cardiovascular disease (CVD) risk factors were tested at baseline and at the end of 10 weeks. Results: A total of 69 participants aged 42.95 (9.27) with metabolic syndrome completed the trial. At the end of current 10-week dietary intervention trial, significant reduction in weight, waist circumference, body fat, visceral fat and waist-hip ratio (WHR) was observed in all four intervention arms (P < 0.001). Also, the observed differences among groups did not reach statistical significance (P > 0.05). Moreover, we found significant reduction in CTRP6 and leptin in all intervention groups (P < 0.001). Reduction of Asprosin level was also marginally significant between intervention groups (P < 0.05). All four intervention groups were found to improve cardiometabolic markers such as FBS, TG, total cholesterol and LDL cholesterol compared to baseline. However, despite clinically significant difference, the within- and between-group changes were not statistically significant at the end of trial. Conclusions: The current RCT in Iranian adults with metabolic syndrome revealed that both moderate and Paleolithic-based low carbohydrate diets with both delivery approaches have comparable beneficial effects in terms of body weight and composition, cardiometabolic factors and metabolism-related adipokines and hepatokines. Trial registration: Available at: https://en.irct.ir/trial/21157, identifier: (IRCT2016121925267N4), Registered on 26 July 2017.